Impact of Human Resources and Technology Support on Management Performance and Product Quality - Doan, Tulus; Nugraha, Evan; Patra, Oviyan (Jurnal Teknologi dan Manajemen, 2025)
Gas turbines are internal combustion engines used as a primary energy source in Gas Power Plants (PLTG). To ensure the reliability and quality of gas turbine repair outcomes, effective project management supported by employee capability and technological infrastructure is essential. This study aims to analyze the influence of employee capability and technological support on project management performance and its subsequent impact on product quality at PT Nusantara Turbin dan Propulsi. A quantitative approach was employed using a descriptive and verification research design, involving 80 research samples. The sample consisted of employees from the operations, marketing, and finance divisions involved in the FT8 gas turbine repair project. Data were collected through Likert-scale questionnaires and analyzed using classical assumption tests, path analysis, t-tests, and F-tests. The results indicate that employee capability and technological support have a positive and significant effect on project management performance (Adjusted R² = 61.6%). Furthermore, the three variables—employee capability, technological support, and project management performance—also significantly influence product quality (Adjusted R² = 80%). Project management performance is proven to be a partial mediator in the relationship between internal capabilities and product quality. These findings emphasize the importance of integrated management of human resources and technological support in project execution to achieve high-quality products